Diokletian und die Tetrarchie Aspekte einer Zeitenwende - Demandt, Alexander; Goltz, Andreas; Schlange-Schöningen, Heinrich (Millennium-Studien / Millennium Studies, 2012)
Renowned scholars from Germany, Great Britain, Croatia, Slovenia and Switzerland contributed to an international conference held in Split in 2003. Their papers collected here show the present state of research on the Tetrarchy in its political, social, economic, ideological, historico-religious and archaeological aspects and on the reception of Diocletian up to modern times.